Study of Chelating Ion Exchange Resin Containing 8-Hydroxy Quinoline and Separation of Metal Ions by Selective Sorption on the Resin Column - A. Shah, Bhavna; V. Shah, Ajay; N. Bhandari, Bharat (Asian Journal of Chemistry, 2010)
Chelating ion exchange resin was synthesised from oxine (8-hydroxy quinoline)-resorcinol-formaldehyde. The physicochemical properties like % moisture content, true density of resin (dres), apparent density of resin (dcol), void volume fraction, total exchange capacity, rate of exchange, interruption test, salt splitting capacity, thermal stability, resin stability, pH study for metal ions, effect of metal ion concentration on exchange capacity were measured. The resin was characterised by IR and TGA. The quantitative separation of copper-nickel. zinc-nickel was accomplished by selective sorption on column.